2020
DOI: 10.1016/j.wneu.2020.05.207
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Exploration of Safe Entry Zones in the Brainstem: Comprehensive Definition and Analysis of the Operative Approach

Abstract: Background: Detailed and accurate understanding of intrinsic brainstem anatomy and the interrelationship between its internal tracts and nuclei and external landmarks is of paramount importance for safe and effective brainstem surgery. Using anatomical models can be an important step in sharpening such understanding.Objective: To show the applicability of our developed virtual 3D model in depicting the safe entry zones (SEZs) to the brainstem.Methods: Accurate 3D virtual models of brainstem elements were creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
(120 reference statements)
0
2
0
Order By: Relevance
“…If the hematoma is close to the surface of the brainstem, color changes or local uplift occurs, and the hematoma cavity can be accessed by cutting the brainstem longitudinally in the local lesion [ 9 , 19 ]. If the hematoma is confined to the brainstem tissue and there is no change on the surface, the hematoma cavity can be accessed through the safe entry zone [ 11 , 12 ]. In addition, during the hematoma clearance, the brainstem supplying arteries and draining veins should be avoided as much as possible so as to avoid iatrogenic injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the hematoma is close to the surface of the brainstem, color changes or local uplift occurs, and the hematoma cavity can be accessed by cutting the brainstem longitudinally in the local lesion [ 9 , 19 ]. If the hematoma is confined to the brainstem tissue and there is no change on the surface, the hematoma cavity can be accessed through the safe entry zone [ 11 , 12 ]. In addition, during the hematoma clearance, the brainstem supplying arteries and draining veins should be avoided as much as possible so as to avoid iatrogenic injury.…”
Section: Discussionmentioning
confidence: 99%
“…With the in-depth study of the anatomical structure and physiological function of the brainstem, it was confirmed that there is a relatively “safe operation area” in the brainstem [ 10 12 ]. Microsurgery is expected to become one of the most important ways to improve the prognosis of SHBSH patients [ 2 , 11 ]. Nevertheless, whether surgical treatment could improve the prognosis of patients with brainstem hemorrhage still remains controversial [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%